Myelodysplastic syndromes (MDS): prognostic factors and scoring systems - Souto, Elizabeth Xisto [UNESP]; Chauffaile, Maria De Lourdes Lopes Ferrari [UNESP]; Moncau, José Eduardo Cajado [UNESP]; Niero-melo, Lígia [UNESP]; Braga, Gisele Wally [UNESP]; Silva, Maria Regina Regis [UNESP]; Kerbauy, José [UNESP] (Associação Paulista de Medicina - APM, 1997)
OBJECTIVE: To evaluate the score systems of Cassano and Sanz and suggest a new one. DESIGN: Case series. LOCATION: Teaching hospitals: EPM UNIFESP and Faculdade de Medicina de Botucatu. PARTICIPANTS: 59 patients diagnosed from 1979 to 1992. INTERVENTION: Evaluation of clinical-laboratorial data. MEASUREMENT: Statistical comparison, uni and multivariate analysis and actuarial survival curves. RESULTS: Cassano's system divided the patients into high and low risk (p=0.0966) while, Sanz's gave high, intermediate and low risk (p=0.0108). The univariate analysis showed hemoglobin, WBC count, E/M ratio, liver size and blast percentage in BM as statistically significant. The multivariate analysis showed blast percentage in BM (p=0.004) and Hb (p=0.050) as significant. Our system, considering the multivariate analysis data, divided the patients into high, intermediate and low risk (p=0.0038). CONCLUSIONS: Sanz's system was more functional than Cassano's, while ours showed predictive survival value and ease of use in clinical practice.

OBJETIVO: Avaliar utilidades dos sistemas de escore de Cassano e Sanz e propor outro. DESENHO: Serie de Casos. LOCAL: Hospitais universitários: EPM-UNIFESP e Faculdade de Medicina de Botucatu. PARTICIPANTES: 59 pacientes diagnosticados entre 1979 e 1992. INTERVENÇÃO: Avaliação de parâmetros clínico-laboratoriais. MENSURAÇÃO: Comparação estatística, análise uni e multivariada e curva de sobrevida atuarial. RESULTADOS: O sistema de Cassano dividiu os pacientes em alto e baixo risco (p=0.0966) enquanto o de Sanz em alto, intermediário e baixo risco (p=0.0108). A análise univariada demonstrou que hemoglobina, contagem de GB, relação EM, aumento do fígado e % de blastos na medula (MO) eram estatisticamente significantes. A regressão multivariada demonstrou como sendo significantes a % de blastos da MO (p=0.004) e os níveis de Hb (p=0.050). O nosso sistema, considerando os parâmetros da análise univariada, dividiu os pacientes em alto, intermediário e baixo risco (p=0.0038). CONCLUSÕES: O sistema de Sanz foi mais prático que o de Cassano enquanto o nosso, demonstrou valor preditivo de sobrevida e uso fácil na prática clínica.
Keywords: Myelodysplastic syndromes; Prognosis; Survival